Tiesiosios žarnos vėžio chirurginis gydymas Ostravos universiteto ligoninėje, Čekijos Respublika - Vavra, Petr; Rydlova, Marie; Pelikan, Anton; Martinek, Lubomir; Gunkova, Petra; Vavrova, Michaela; Gunka, Igor (Lietuvos chirurgija, 2004)
Petr Vavra1, Marie Rydlova3, Anton Pelikan1, Lubomir Martinek1, Petra Gunkova1, Michaela Vavrova2, Igor Gunka1 1 Department of Surgery and 2 Department of Radiology, University Hospital of Ostrava, 3 Department of Pathology, Medical-Social Faculty of University of Ostrava, 17 listopadu 1790, 708 52 Ostrava Poruba, Czech Republic E-mail: p_vavra@quick.cz Background / objective Czech Republic is among the countries with the highest incidence of rectal cancer. The aim of the prospective study was to monitor the surgical treatment of patients with the diagnosis of rectal cancer. Patients and methods 188 patients (121 males and 67 females) with rectal cancer were operated on within the period of three years (2000–2002). The definitive analysis encompassed 171 patients. The following aspects were observed: the types of operations carried out, the safety distance of the lower resection line during the operation of rectal cancer mainly, the amount of lymphatic nodes spotted in the mesorectum and the possibility of their laparoscopic treatment. Results 129 patients were operated on by conventional methods and 42 patients (24.6%) by laparoscopical methods (25 anterior resections, 6 abdominoperineal amputations, 10 colostomies, 1 proctocolectomy). At a distance of 2 mm from the aboral edge of the tumour, the distal intramural spread of cancer was detected in 8 (11.8%), at 5 mm in 6 (9%), at 1 cm in 2 (2.6%), at 2 cm in 4 patients (5.8 %) and at 5 cm from the macroscopical edge no distal intramural spread was recorded. Enlarged lymphatic nodes were discovered in 128 patients. In total, there were 1383 lymphatic nodes, i.e. 10.8 lymphatic nodes per patient. 271 lymphatic nodes (19.5%) affected by a tumour process, i.e. 2.1 affected lymphatic nodes per patient were found. The number of the affected lymphatic nodes in the mesorectum was compared in connection with the usage of conventional or laparascopical operation. There was no difference in oncological radicality as far as these types of operations are concerned. Conclusions There is no evidence of the spread of well differentiated adenocarcinoma from the aboral edge of the tumour. All positive findings of distal intramural spread were found in the medium and lower differentiated adenocarcinomas. The distal intramural spread of the tumour is quite rare, but when present it signifies a very advanced and aggressive progress of the illness with a bad prognosis. It is too early to formulate the conclusions comparing the conventional and the laparoscopic approaches to rectal cancer.